2021
DOI: 10.1002/nop2.884
|View full text |Cite
|
Sign up to set email alerts
|

Body image and hopelessness among early‐stage breast cancer survivors after surgery in China: A cross‐sectional study

Abstract: Worldwide, breast cancer is the most common cancer among women (Ferlay et al., 2015). Based on data from the Global Cancer Statistics 2018, it accounted for nearly 2.1 million newly diagnosed cancer cases in 185 countries (Bray et al., 2018). In China, from 2009 to 2011, breast cancer cases were estimated to be around 15.1% of all newly diagnosed cancer cases (Chen et al., 2016), and it is predicted that 2.5 million new cases of breast cancer will be diagnosed among Chinese women by 2021 (Linos et al., 2008). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 58 publications
2
14
1
1
Order By: Relevance
“…Most of the participants in this study placed little importance on body image, which differs from other studies (Kołodziejczyk & Pawłowski, 2019; Wu et al, 2021) that found self-esteem to be negatively affected by poor body image in patients with BrCa. In other words, body image has been reported to enhance self-efficacy and self-esteem.…”
Section: Discussioncontrasting
confidence: 99%
“…Most of the participants in this study placed little importance on body image, which differs from other studies (Kołodziejczyk & Pawłowski, 2019; Wu et al, 2021) that found self-esteem to be negatively affected by poor body image in patients with BrCa. In other words, body image has been reported to enhance self-efficacy and self-esteem.…”
Section: Discussioncontrasting
confidence: 99%
“…In study, the Beck Hopelessness score of caregivers of patients with cancer patients was 10.47 ± 5.32, which is consistent with the research results of previous studies [4] . This score indicates that the hopelessness level of caregivers of cancer patients is high, and the scores of the F-14, RTS, and PSQI were all signi cantly higher than those of normal people in China [14] .…”
Section: Family Caregivers Have a Level Of Hopelessnesssupporting
confidence: 91%
“…Wu et al conducted a study to determine body image and hopelessness among earlystage breast cancer survivors after surgery in China. The results of the study showed that body image was significantly and positively associated with and had a positive effect on hopelessness [29].…”
Section: Discussionmentioning
confidence: 91%